Clinical aspects of the treatment of atopic dermatitis with topical glucocorticoids and calcineurin inhibitors — a pilot questionnaire study - Hałubiec, Przemysław; Jaworek, Andrzej Kazimierz; Wojas-Pelc, Anna (Folia Medica Cracoviensia, 2023)
Atopic dermatitis (AD) is the most common inflammatory skin disease. However, recent reports concerning the simple clinical aspects of treatment with topical glucocorticosteroids (TCS) and calcineurin inhibitors (TCI) are lacking. The objective of this study is providing an update on these characteristics of AD management. A group of 150 adults suffering from AD treated with TCS during last year was asked to fill an anonymous questionnaire. The course of topical treatment was analyzed in the context of the severity of symptoms and the knowledge of the patients about therapy. During the last year, the majority of patients (66%) were treated with class IV TCS; however, in the last two weeks, class I TCS was used the most frequently (35%). Only 11% were familiar with the concept of intermittent therapy and 4% used the fingertip unit (FTU). In total, 77% of them used TCI. Most of the patients used the same class of TCS permanently. Unfortunately, patients are unaware of simple approaches (like intermittent therapy or FTU) that increase both the effectiveness and safety of the treatment. Practicians should be aware of these problems to identify and eliminate them, primarily through the education of patients.
Keywords: atopic dermatitis; topical glucocorticosteroids; topical calcineurin inhibitors; finger tip unit; intermittent therapy